2005
DOI: 10.1016/j.bcp.2005.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Role of P-glycoprotein in transplacental transfer of methadone

Abstract: Methadone is the therapeutic agent of choice for treatment of the pregnant opiate addict. However, little is known on the factors affecting its concentration in the fetal circulation during pregnancy and how it might relate to neonatal outcome. Therefore, a better understanding of the function of placental metabolic enzymes and transporters should add to the knowledge of the role of the tissue in the disposition of methadone and its relation to neonatal outcome. We hypothesized that the expression and activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 29 publications
1
50
0
Order By: Relevance
“…However, the transfer of indinavir was unaffected in the presence of ritonavir, most likely because of low P-gp inhibitory potential of ritonavir at clinically relevant concentrations (42). Like indinavir (42) and saquinavir (79) (see above), methadone (80) also showed increased fetal drug transfer after inhibition of P-gp in the perfused human placenta. Nekhayeva et al also reported that MDR1 has been demonstrated to regulate the disposition of methadone across the placental barrier in the perfused human placental model (81).…”
Section: Abc Transporters In the Placentamentioning
confidence: 99%
“…However, the transfer of indinavir was unaffected in the presence of ritonavir, most likely because of low P-gp inhibitory potential of ritonavir at clinically relevant concentrations (42). Like indinavir (42) and saquinavir (79) (see above), methadone (80) also showed increased fetal drug transfer after inhibition of P-gp in the perfused human placenta. Nekhayeva et al also reported that MDR1 has been demonstrated to regulate the disposition of methadone across the placental barrier in the perfused human placental model (81).…”
Section: Abc Transporters In the Placentamentioning
confidence: 99%
“…The intra/extra cellular ratio of methadone was significantly decreased in human ABCB1 transfected cells relative to controls (140). An in vitro model of transplacental transport found that P-gp inhibitor GF120918 increased the transfer of methadone by 30%, and that uptake of methadone in the BeWo cell line was increased in the presence of P-gp inhibitor cyclosporine A (141). The same group demonstrated that methadone transfer was significantly higher in the fetal-tomaternal direction, likely due to the unidirectional activity of P-gp (142).…”
Section: Methadonementioning
confidence: 94%
“…Pgp is known to show extremely broad substrate specificity, including peptides, steroids, therapeutic drug from very large and complex ones as paclitaxel [178] to relatively simple as phenytoin, opioids, and other analgesics [179] or even ions [180–186]. Substrates are often, but not always (e.g., colchicine), amphipathic and relatively hydrophobic.…”
Section: Drug Transportmentioning
confidence: 99%